Reason and Revelation According to Harun Nasution and Quraish Shihab and its Relevance to Islam Education - Furqan, Furqan; Hikmawan, Arham (Al-Misbah (Jurnal Islamic Studies), 2021)
The theme of reason and revelation becomes a hot topic because it is one of the Islamic theology studies that cannot be separated from a polemic. The use of reason is more dominant than a divine revelation will tend to produce a liberal. However, reasoning that ignores a reason will tend to be textual and traditional. The research aims to find out the comparison between the thought of Harun Nasution and Muhammad Quraish Shihab about reason and revelation and its relevance with Islam Education. While this research is theoretically used to enrich the scientific treasures of reason and revelation. The result presents the difference and similarity between both figures’ thoughts on reason and revelation. Harun Nasution and Muhammad Quraish Shihab believe in an absolute truth that only comes from a divine revelation. Humans’ reason has extraordinary potential if it is used appropriately. However, it also has a tendency to drive to an astray way. Besides, both figures emphasize on the moral function of the divine revelation towards human life. The divine revelation brings goodn values for mankind through their lives. The difference is in the capacity in providing an area for reason and revelation. Harun Nasution tends to give a bigger portion to use the reason than the divine revelation in formulating his opinions. Meanwhile, Quraish Shihab is known as a moderate figure because their opinion prioritizes the harmony between reason and revelation.